Video-Enhanced Telemedicine Improves the Care of Acutely Injured Burn Patients in a Rural State. Issue 6 (November 2016) - Wibbenmeyer, Lucy; Kluesner, Karen; Wu, Hongqian; Eid, Anas; Heard, Jason; Mann, Benjamin; Pauley, Alison; Peek-Asa, Corrine
Abstract : The acute care of burn patients is critical and can be a daunting experience for emergency personnel because of the scarcity of burn injuries. Telemedicine that incorporates a visual component can provide immediate expertise in the treatment and management of these injuries. The authors sought to evaluate the addition of video telemedicine to our current telephone burn transfer program. During a 2-year period, 282 patients, 59.4% of all burn patients transferred from outside hospitals, were enrolled in the study. In addition to the scripted call with the charge nurse (ChargeRN) and the accepting physician, nine hospitals also transmitted video images of the wounds before transfer as part of a store and forward telemedicine transfer program (77, 27.6%). The accuracy of burn size estimations (BSA burned) and management changes (fluid requirements, transfer mode, and final disposition) were analyzed between the telephones-only sites (T only) and the video-enhanced sites. Referringstaff participating in video-enhanced telemedicine were sent a Google survey assessing their experience the following day. The referring staff (Referringstaff) was correct in their burn assessment 20% of the time. Video assessment improved the ChargeRN BSA burned and resulted in more accurate fluid resuscitation ( P = .030), changes in both transportation mode ( P = .042), and disposition decisions ( P = .20). The majority of the Referringstaff found that video-enhanced telemedicine helped them communicate with the burn staff more effectively (3.4 ± 0.37, scale 1–4). This study reports the successful implementation of video-enhanced telemedicine pilot project in a rural state. Video-enhanced telemedicine using a store and forward process improved burn size estimation and facilitated management changes. Although not quantitatively assessed, the low cost of the system coupled with the changes in transportation and disposition strongly suggests a decrease in healthcare costs associated with the addition of video to a telephone-only transfer program.